2007
DOI: 10.1002/jsfa.2767
|View full text |Cite
|
Sign up to set email alerts
|

Associations between grain characteristics and alcohol yield among soft wheat varieties

Abstract: Samples of ten winter wheat varieties, grown at four locations on the eastern side of the UK were assessed for alcohol yield. There was a strong negative association between alcohol yield and grain nitrogen content, but this was strongly influenced by differences between the sites, with a range of alcohol yields observed at given nitrogen levels. Inclusion of grain size parameters, thousand grain weight and grain length:width ratio, along with nitrogen, in a multiple regression, enabled more accurate predictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 20 publications
6
27
1
1
Order By: Relevance
“…A negative correlation between grain N content and ethanol yield has previously been reported (Daniel et al, 2008;Swanston et al, 2005Swanston et al, , 2007. Kevin Hicks (2005) reported that high starch content is needed to produce ethanol.…”
Section: Correlation Analysis Of Grain and Agronomic Characteristicsmentioning
confidence: 75%
“…A negative correlation between grain N content and ethanol yield has previously been reported (Daniel et al, 2008;Swanston et al, 2005Swanston et al, , 2007. Kevin Hicks (2005) reported that high starch content is needed to produce ethanol.…”
Section: Correlation Analysis Of Grain and Agronomic Characteristicsmentioning
confidence: 75%
“…Lacerenza et al [2008] recently pointed out that the traditional selection criteria for wheat-breeding, based on milling and baking quality, is not consistent with maximal ethanol yield per hectare. The lack of breeding programs for varieties designed specifically for ethanol production, suggests Swanston et al [2007], is due to a lack of appropriate selection procedures due to limited understanding of the factors contributing to alcohol yield. Recent research into optimized bioethanol production has focused on the development of new and improved cereal and maize hybrids with higher starch contents to increase ethanol yields [Wu et al, 2006].…”
Section: Cereal Starch Characteristics Optimal For Bioethanol Feedstockmentioning
confidence: 99%
“…Most of the distilleries especially those which produce products for export prefer to use ethyl alcohol produced from wheat [10][11][12].…”
Section: Introductionmentioning
confidence: 99%